Biomarkers of Presbycusis and Tinnitus in a Portuguese Older Population - Haider, Haúla F.; Flook, Marisa; Aparicio, Mariana; Ribeiro, Diogo; Antunes, Marilia; Szczepek, Agnieszka J.; Hoare, Derek J.; Fialho, Graça; Paço, João C.; Caria, Helena (Frontiers in Aging Neuroscience, 2017)
Introduction: Presbycusis or age-related hearing loss (ARHL) is a ubiquitous health problem. It is estimated that it will affect up to 1.5 billion people by 2025. In addition, tinnitus occurs in a large majority of cases with presbycusis. Glutamate metabotropic receptor 7 (GRM7) and N-acetyltransferase 2 (NAT2) are some of the genetic markers for presbycusis. Objectives: To explore patterns of hearing loss and the role of GRM7 and NAT2 as possible markers of presbycusis and tinnitus in a Portuguese population sample. Materials and Methods: Tonal and speech audiometry, tinnitus assessment, clinical interview, and DNA samples were obtained from patients aged from 55 to 75 with or without tinnitus. GRM7 analysis was performed by qPCR. Genotyping of single nucleotide polymorphisms (SNPs) in NAT2 was performed by PCR amplification followed by Sanger sequencing or by qPCR. Results: We screened samples from 78 individuals (33 men and 45 women). T allele at GRM7 gene was the most observed (60.3% T/T and 33.3% A/T). Individuals with a T/T genotype have a higher risk for ARHL and 33% lower risk for tinnitus, compared to individuals with A/A and A/T genotype, respectively. Being a slow acetylator (53%) was the most common NAT2 phenotype, more common in men (55.8%). Intermediate acetylator was the second most common phenotype (35.9%) also more frequent in men (82.6%). Noise exposed individuals and individuals with ‘high frequency’ hearing loss seem to have a higher risk for tinnitus. Our data suggests that allele AT of GRM7 can have a statistically significant influence towards the severity of tinnitus. Conclusion: For each increasing year of age the chance of HL increases by 9%. The risk for ARHL was not significantly associated with GRM7 neither NAT2. However we cannot conclude from our data whether the presence of T allele at GRM7 increases the odds for ARHL or whether the A allele has a protective effect. Genotype A/T at GRM7 could potentially be considered a biomarker of tinnitus severity. This is the first study evaluating the effect of GRM7 and NAT2 gene in tinnitus.